Phage therapy as an alternative strategy for oral bacterial infections: a systematic review - Mingqi Zhu; Chunxiu Hao; Ting Zou; Shan Jiang; Buling Wu (BMC Oral Health)
Abstract Background Oral infectious diseases, such as dental caries, periodontitis and periapical periodontitis, are often complicated by causative bacterial biofilm formation and significantly impact human oral health and quality of life. Bacteriophage (phage) therapy has emerged as a potential alternative with successful applications in antimicrobial trials. While therapeutic use of phages has been considered as effective treatment of some infectious diseases, related research focusing on oral infectious diseases is few and lacks attention. Therefore, a systematic review was conducted to comprehensively evaluate the overall efficacy of phages in reducing bacterial infections associated with various oral diseases. Methods A systematic search of PubMed, MEDLINE and Web of Science for literature published up to May 2024 was conducted according to inclusion criteria to identify studies assessing bacteriophages as potential therapy for oral infectious diseases. A total of four authors assessed study eligibility and performed data extraction. Results A total of 487 articles published between 1975 and 2024 were retrieved. Among the 10 eligible reports, preliminary studies have been conducted on seven types of phages and reported their antibacterial effect. To be more specific, 3 contained data on dental caries (n = 32), 5 focused on periodontitis (n = 105) and 2 examined periapical diseases (n = 7). The majority of publications (9 out of 10) discussed the impact of phages on biofilm formation. Only one report (1 out of 10) mentioned the safety concern in phage application. Conclusions This review strongly suggests that phages isolated from oral cavity with certain characteristics can be highly effective and are considered suitable candidates for phage therapy in treating oral/odontogenic infections caused by bacteria.